Regulation of Inducible Potassium Transporter KdpFABC by the KdpD/KdpE Two-Component System in Mycobacterium smegmatis - Ali, Maria K.; Li, Xinfeng; Tang, Qing; Liu, Xiaoyu; Chen, Fang; Xiao, Jinfeng; Ali, Muhammad; Chou, Shan-Ho; He, Jin (Frontiers in Microbiology, 2017)
Kdp-ATPase is an inducible high affinity potassium uptake system that is widely distributed in bacteria, and is generally regulated by the KdpD/KdpE two-component system. In this study, conducted on Mycobacterium smegmatis, the kdpFABC expression was found to be affected by low concentration of K+, high concentrations of Na+, and/or NH4+ of the medium. The KdpE was found to be a transcriptional regulator that bound to a specific 22-bp sequence in the promoter region of kdpFABC operon to positively regulate kdpFABC expression. The KdpE binding motif was highly conserved in the promoters of kdpFABC among the mycobacterial species. 5'-RACE data indicated a transcriptional start site of the kdpFABC operon within the coding sequence of MSMEG_5391, which comprised a 120-bp long 5'-UTR and an open reading frame of the 87-bp kdpF gene. The kdpE deletion resulted in the altered growth rate under normal and low K+ conditions. Furthermore, under K+ limiting conditions, a single transcript (kdpFABCDE) spanning both kdpFABC and kdpDE operons was observed. This study provided the first insight into the regulation of kdpFABC operon by the KdpD/KdpE two-component system in M. smegmatis.